Socio-behavioral dysfunction in disorders of hypothalamic-pituitary involvement: The potential role of disease-induced oxytocin and vasopressin signaling deficits. (September 2022) - Clarke, Lauren; Zyga, Olena; Pineo-Cavanaugh, Psalm L.; Jeng, Michael; Fischbein, Nancy J.; Partap, Sonia; Katznelson, Laurence; Parker, Karen J.
Abstract: Disorders involving hypothalamic and pituitary (HPIT) structures—including craniopharyngioma, Langerhans cell histiocytosis, and intracranial germ cell tumors—can disrupt brain and endocrine function. An area of emerging clinical concern in patients with these disorders is the co-occurring socio-behavioral dysfunction that persists after standard hormone replacement therapy. Although the two neuropeptides most implicated in mammalian social functioning (oxytocin and arginine vasopressin) are of hypothalamic origin, little is known about how disease-induced damage to HPIT structures may disrupt neuropeptide signaling and, in turn, impact patients' socio-behavioral functioning. Here we provide a clinical primer on disorders of HPIT involvement and a review of neuropeptide signaling and socio-behavioral functioning in relevant animal models and patient populations. This collective evidence suggests that neuropeptide signaling disruptions contribute to socio-behavioral deficits experienced by patients with disorders of HPIT involvement. A better understanding of the biological underpinnings of patients' socio-behavioral symptoms is now needed to enable the development of the first targeted pharmacological strategies by which to manage patients' socio-behavioral dysfunction. Highlights: Social dysfunction can occur in disorders of hypothalamic-pituitary involvement. Disorders include: craniopharyngioma, Langerhans cell histiocytosis, and germinomas. Hypothalamic oxytocin and vasopressin signaling are critical for social function. Hypothalamic oxytocin and vasopressin signaling may be disrupted in these disorders. These pathways may be therapeutic targets for improving patients' social function.